Resolving the Contradiction between National and Supranational Interests as an Instrument of Realizing Regional Integration Potential - A. V. Khramova (Евразийская интеграция: экономика, право, политика, 2022)
This study is aimed to investigate the key problem of any integration association — the contradiction between national and supranational interests — and the practice of overcoming it in the European Union (EU), the Association of Southeast Asian Nations (ASEAN) and the Eurasian Economic Union (EAEU).Aim. Offer recommendations for realizing the potential of the EAEU by resolving the contradiction between national and supranational interests.Tasks. Consider models for overcoming the contradiction between national and supranational interests in the integration associations of the EU and ASEAN, characterize the situation in the EAEU and propose successful practices of the EU and ASEAN to try to solve this problem.Methods. To compare the integration practices of the EU and ASEAN, the method of comparative analysis is used. As for the EAEU, it is proposed to use the best practices of both associations, which make it possible to make methods of analysis, synthesis, generalization, as well as the SMART goalsetting method.Results. On the basis of specific examples, recommendations are given for combining soft and hard approaches for the development of the EAEU with the prospect of building a Greater Eurasian partnership in the future. Thus, the EAEU should pay attention to the experience of the EU in terms of strengthening the supranational structure of the association, as well as to the practice of ASEAN dialogue mechanisms. At the same time, following the example of the EU, one should not create an excessive bureaucracy and exert excessive pressure on countries by interfering in their internal affairs. In order to effectively set goals, the EAEU should apply the technologies of the SMART method, which provides for the setting of specific, measurable, achievable, meaningful and timelimited goals.Conclusion. The contradiction between national and supranational interests is the most profound problem in any integration association, including the EAEU. However, there is no universal method for resolving this problem. The EAEU should combine in its practice the experience of the EU and ASEAN as hard and soft approaches to balancing national and supranational interests.